Reformation in the Financial Management of Community Colleges in Makawanpur District of Nepal - Upadhyay, Shankar Prasad; Manandhar, Rachana; Paudel, Sushil; Phuyal, Meghraj; Dahal, Ashish; Pokharel, Ghanashyam (A Peer Reviewed Journal on Social Sciences, 2024)
Financial management of higher academic institutions in Nepal involves several key aspects to ensure sustainability and effective operation. The main aim of the research was to find out the financial performance of community campuses in Nepal. Based on purposive sampling and quantitative data collected from the campus, the research was concluded. Both statistical and financial tools; growth rate trend, mean, coefficient of correlation and budgetary performance comparison were used for the analysis of data. The study captured coefficient of correlation between recurrent expenditure and internal revenue and external revenue, growth rate and its trend, and mean of revenue, revenue expenditures, and average growth rate of recent past five fiscal years of Hetauda Campus. There was substantial correlation between internal revenue and recurrent expenditure (r = + 0.78) and highly correlation between total revenue and recurrent expenditure (r = + 0.88). The average growth rate of internal revenue was 9.93 percent whereas, the growth rate of recurrent expenditure was 13.73 percent (9.93≤13.73). The growth rate of internal revenue was in decreasing trend. The analysis indicated that the financial performance of Hetauda campus was impoverished and it directed that the financial management performance of Nepalese community colleges was weak throughout the study period of five years (viz. 2075/076 to 2079/080 AD) and contemporary reformation in the management of finance was appreciable.